Konsep Kafa’ah Untuk Menentukan Calon Pasangan Dalam Membentuk Keharmonisan Rumah Tangga - Wahyudi, Nano; Tanjung, Dhiauddin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The achievement of the goal of marriage is not absolutely determined by the balance or comparability factor alone, but this can be the main support, and it is the religious and moral aspects that are more important and must be prioritized in creating a harmonious and better household guaranteeing the safety of the fostered household life.